2018
DOI: 10.1111/jfs.12576
|View full text |Cite
|
Sign up to set email alerts
|

Survival of food‐borne bacterial pathogens in traditional Mediterranean anchovy products

Abstract: The aim of this study was to investigate the survival of Salmonella Enteritidis, Staphylococcus aureus and Listeria monocytogenes in salted and marinated anchovy (Engraulis encrasicholus). Total viable counts (TVCs), lactic acid bacteria, Enterobacteriaceae, and yeasts/molds were also enumerated. Initially, TVC was as high as 5.5 log10 cfu/g, but the population dropped down to 3.2 and 2.2 log10 CFU/g for salted and marinated anchovy, respectively. S. aureus was the most salt‐tolerant and L. monocytogenes was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…This decrease in total bacteria level is due to salt and acid used in the marination process. Similar results were reported by (Kilinc et al, 2005b;Verdos et al, 2019). Tomac et al (2015) reported the initial count of mesophilic bacteria in frozen anchovies as 3.87 log cfu/g, 2.58 log cfu/g after marination.…”
Section: Microbiological Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…This decrease in total bacteria level is due to salt and acid used in the marination process. Similar results were reported by (Kilinc et al, 2005b;Verdos et al, 2019). Tomac et al (2015) reported the initial count of mesophilic bacteria in frozen anchovies as 3.87 log cfu/g, 2.58 log cfu/g after marination.…”
Section: Microbiological Analysissupporting
confidence: 86%
“…With the marination process Enterobacteriaceae count decreased due to salt and vinegar. Enterobacteriaceae is often used as a sign of post-process contamination of fecal contamination (Verdos et al, 2019). Enterobacteriaceae count increased till 2 nd month of storage and decreased afterward for garlic added group.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…The marinated products had a pH well below 5, making the risk of Clostridium botulinum Type E, negligible; for this reason, the MAP with oxygen inclusion was not used. The main risk of these products could be other food-borne pathogens with the most important the Listeria monocytogenes , but the low pH of our products can definitely inhibit growth and might be able to inactivate such bacteria [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the risk of S. aureus in Saeu-jeot was low; however, the confirmed contamination with S. aureus indicated poor hygiene management in the workplace. In addition, S. aureus proliferates if the salt is diluted and, if the product is left unattended for long periods at room temperature, it can also contaminate the product [21]. Therefore, the steps of the manufacturing process should be investigated to identify the causes of and control S. aureus contamination.…”
Section: Prediction Of the S Aureus Contamination Level Based On The ...mentioning
confidence: 99%